Police body-worn cameras and privacy: Views and concerns of officers and citizens - Poirier, Brigitte (International journal of police science & management, 2024)
Police body-worn cameras (BWC) have been lauded for their potential to increase transparency and accountability by documenting officers’ actions and interactions with citizens. However, despite their widespread use in recent years, several law enforcement agencies have been hesitant to adopt this technology because of privacy concerns. This article explores the views of police officers and citizens from the Canadian province of Quebec towards the use of BWCs. Specifically, it seeks to: (a) understand how officers feel about being monitored by BWCs and (b) assess citizens’ privacy concerns towards police BWCs. A mixed-method research design was used, including interviews and focus groups with 78 police officers, including 46 officers from four pilot sites, and a telephone survey of 1609 residents from the same sites. The results show that officers are concerned about the potential effects of BWCs on their privacy and the privacy of the public. One major area of concern is the impact it may have on their work performance and the use of adaptative measures that support them in carrying out challenging duties. By contrast, most citizens have no reservations about being recorded by a BWC. Certain individual characteristics—such as age and perceptions of the police—however, were associated with heightened privacy concerns. Without neglecting citizens’ privacy, this study provides insights into the development of BWC policies that preserve officers’ right to privacy and ability to fulfill their duty.